Hardware support for early register release. (11th November 2005) - Monreal, Teresa; Vinals, Víctor; Gonzalez, Antonio; Valero, Mateo
Register files are becoming one of the critical components of current out-of-order processors in terms of delay and power consumption, since their potential to exploit instruction-level parallelism is closely related to the size and number of ports of the register file. In conventional register-renaming schemes, register releasing is conservatively done only after the instruction that redefines the same register is committed. Instead, we propose a scheme that releases registers as soon as the processor knows that there will be no further use of them. We present two early releasing hardware implementations with different performance/complexity trade-offs. Detailed cycle-level simulations show either a significant speedup for a given register file size, or a reduction in register file size for a given performance level.